Investigating Teachers’ Work with Digital Resources. A Comparison Between the Teaching of Mathematics and English - Gruson, Brigitte; Gueudet, Ghislaine; Hénaff, Carole Le; Lebaud, Marie-Pierre (Revue suisse des sciences de l'éducation, 2018)
The abundant digital resources on the Internet are leading to profound changes in teachers’ activity. We refer to the theoretical framework and methodology of the documentational approach to didactics to investigate these changes. We compare two case studies: an English teacher, and a mathematics teacher, both working in the same upper secondary school in France. We have observed significant use of digital resources in both cases, but of a different nature. We present and discuss these differences that shed light upon teachers’ documentational work. We use these cases to draw more general conclusions on designing, using and sharing digital teaching resources.
Number: 2
Keywords: Comparative didactics; digital resources; documentational approach; teachers’ resources; upper secondary school